2004
DOI: 10.1007/s00170-003-1833-5
|View full text |Cite
|
Sign up to set email alerts
|

A bidirectional heuristic for stochastic assembly line balancing Type II problem

Abstract: In this paper, a heuristic algorithm is proposed to solve the single-model stochastic assembly line balancing Type II problem. For a given number of workstations and a pre-specified assembly line reliability, which is the probability of the workload not exceeding the cycle time for the whole assembly line, the proposed algorithm tries to obtain a solution with the smallest cycle time. In the first stage, the tasks are assigned to workstations from the forward and backward directions alternatively. In the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Two heuristic approaches to the assembly line re-balancing problem were developed in (Gamberini, Gebennini, Grassi, & Regattieri, 2009;Gamberini, Grassi, & Rimini, 2006). In Liu, Ong, and Huang (2005), the authors studied the problem of minimizing the cycle time of the line to be designed.…”
Section: Assembly Line Design and Balancingmentioning
confidence: 99%
“…Two heuristic approaches to the assembly line re-balancing problem were developed in (Gamberini, Gebennini, Grassi, & Regattieri, 2009;Gamberini, Grassi, & Rimini, 2006). In Liu, Ong, and Huang (2005), the authors studied the problem of minimizing the cycle time of the line to be designed.…”
Section: Assembly Line Design and Balancingmentioning
confidence: 99%
“…See for example, Baykasoglu and Dereli (2009), Simaria and Vilarinho (2009), Kara and Tekin (2009), Yagmahan (2011), Xu and Xiao (2011), Chutima and Chimklai (2012, Hamzadayi and Yildiz (2012), Rabbani et al (2012), Liao et al (2012), Akpinar et al (2013), Kucukkoc et al (2013), Manavizadeh et al (2013 and Kucukkoc and Zhang (2015a, 2015b, 2014a for recently published studies on type-I problems; and Hackman et al (1989), Simaria and Vilarinho (2004), Liu et al (2004), Battini et al (2007), Ozcan et al (2011) and Yoosefelahi et al (2012) for studies published on type-II problems.…”
Section: Assembly Lines Can Be Classified As Single-model Lines Mixementioning
confidence: 99%
“…Their methodology was based on DP and branch-and-bound procedure. Also several studies on other type assembly line balancing problems have been reported in the literature: for mixed model (Xiaobo et al [ [22] proposed a heuristic algorithm to solve the type-2 stochastic assembly line balancing problem.…”
Section: Literature Reviewmentioning
confidence: 99%